Usefulness of IMP3 and FOXP3 to predict metastasis of cutaneous melanomas - Juliana Polizel Ocanha-Xavier; José Cândido C. Xavier-Junior; Mariângela Esther Alencar Marques (BMC, 2018)
Abstract Background Melanoma still has considerable mortality in spite of improvements in diagnosis and treatment. Unfortunately, current diagnostic procedures cannot predict precisely its biological behavior, what urges specialists in searching new better biomarkers of lousy prognosis. The objective of the study was to evaluate IMP3 and FOXP3 expression in primary skin melanoma lesions and to correlate with the presence of metastasis. Methods A retrospective cohort study analyzed 112 patients diagnosed with Melanoma, from 2003 to 2011, from a public health service. Samples from the primary lesion were analyzed by two pathologists and one dermatologist to ensure histological subtype, Breslow, the presence of ulceration, mitosis and histological regression. From the species stored, FOXP3 and IMP3 immunohistochemistry staining were performed. Demographic, clinical and evolution aspects of the patients were obtained from records, in the year of 2015. It was considered statistically significant when p-value < 0.05. Results The majority of specimens had 25% or fewer cells stained with FOXP3 or IMP3. Their positivity could not be related to the occurrence of metastasis (p = 0.947 and p = 0.936, respectively). Conclusion There is no evidence of benefit in using IMP3 or FOXP3 as prognostic markers in primary melanomas in our population.